MGMT promoter methylation is associated with temozolomide response and prolonged progression‐free survival in disseminated cutaneous melanoma. Issue 12 (24th November 2014) - Tuominen, Rainer; Jewell, Rosalyn; van den Oord, Joost J.; Wolter, Pascal; Stierner, Ulrika; Lindholm, Christer; Hertzman Johansson, Carolina; Lindén, Diana; Johansson, Hemming; Frostvik Stolt, Marianne; Walker, Christy; Snowden, Helen; et al.
<x xml:space="preserve">Abstract</x> To investigate the predictive and prognostic value of O6‐methylguanine DNA methyltransferase (MGMT) inactivation by analyses of promoter methylation in pretreatment tumor biopsies from patients with cutaneous melanoma treated with dacarbazine (DTIC) or temozolomide (TMZ) were performed. The patient cohorts consisted of Belgian and Swedish disseminated melanoma patients. Patients were subdivided into those receiving single‐agent treatment with DTIC/TMZ (cohort S, n = 74) and those treated with combination chemotherapy including DTIC/TMZ (cohort C, n = 79). Median follow‐up was 248 and 336 days for cohort S and cohort C, respectively. MGMT promoter methylation was assessed by three methods. The methylation‐related transcriptional silencing of MGMT mRNA expression was assessed by real‐time RT‐PCR. Response to chemotherapy and progression‐free survival (PFS) and overall survival were correlated to MGMT promoter methylation status. MGMT promoter methylation was detected in tumor biopsies from 21.5 % of the patients. MGMT mRNA was found to be significantly lower in tumors positive for MGMT promoter methylation compared to tumors without methylation in both treatment cohorts (p < 0.005). DTIC/TMZ therapy response rate was found to be significantly associated with MGMT promoter methylation in cohort S (p = 0.0005), but did not reach significance in cohort C (p = 0.16). Significantly longer PFS was observed among patients with MGMT promoter‐methylated tumors (p = 0.002). Multivariate Cox regression analysis identified presence of MGMT promoter methylation as an independent variable associated with longer PFS. Together, this implies that MGMT promoter methylation is associated with response to single‐agent DTIC/TMZ and longer PFS in disseminated cutaneous melanoma.